INCORPORATING EDMODO AS LEARNING MANAGEMENT SYSTEM OF SUMMATIVE ASSESSMENT IN EFL CLASSROOM - Nadia Fauzatus Sabila; Muhammad Reza Pahlevi; Fauzi Miftakh (Eltin Journal : Journal of English Language Teaching in Indonesia, 2020)
This present study aims to find out how an English teacher carries out Edmodo in summative assessment and to find out students’ perceptions doing online assessment through Edmodo in EFL classroom. This basic interpretive study involved thirty students of one of senior high schools in Karawang. The data were collected from the subject of this research directly even via google form and whatsapp by using some instruments, such as: observation sheet, interview guideline, and questionnaire. The present study used semi-structured interview for three interviewees via whatsapp. The researchers also distributed close-ended questionnaire via google form to thirty students. Then, it was analyzed by using Miles and Huberman’s method of data analysis. The finding indicated that the teacher conducts an online assessment using Edmodo with appropriate procedures. Edmodo leads teacher and students’ technological knowledge and Edmodo renders the test practical and motivating. The students perceived Edmodo well as summative assessment although there was a few negative assumption. Most students would prefer to be evaluated through Edmodo instead of the traditional test or paper-based test.  Keywords: keyword Edmodo, online assessment, summative assessment